Museums and the ancient Middle East: curatorial practice and audiences - Emberling, Geoff; Petit, Lucas Pieter (Routledge research in museum studies, 2019)
Museums and the Ancient Middle East is the first book to focus on contemporary exhibit practice in museums that present the ancient Middle East. Bringing together the latest thinking from a diverse and international group of leading curators, the book presents the views of those working in one particular community of practice: the art, archaeology, and history of the ancient Middle East. Drawing upon a remarkable group of case studies from many of the world's leading museums, including the British Museum, the Louvre, the Metropolitan Museum of Art, the Ashmolean Museum, and the Vorderasiatisches Museum in Berlin, this volume describes what curators have done in order to present a previously unseen side of the Middle East region and its history. Highlighting overlaps and distinctions between the practices of national, art and University museums around the globe, the contributors to the volume are also able to offer a unique insight into the types of challenges and opportunities facing the 21st-century curator. Museums and the Ancient Middle East should be of interest to academics and students engaged in the study of museums and heritage, archaeology, the ancient Near East, Middle Eastern studies and ancient history. The unique insights provided by curators active in the field ensure that the book should also be essential reading for museum practitioners around the globe